The Effectiveness of the Android-Based Calistung Digital Game Application to Improve Early Childhood Cognitive Skills - Evi Selva Nirwana (AL-ISHLAH: Jurnal Pendidikan, 2021)
This article aims to determine Android-based digital calistung game application's effectiveness to improve early childhood cognitive skills. The experimental method was carried out on 26 kindergarten students aged 5-6 years. The research design used was pre-experimental. The sampling technique used in this study was purposive sampling. Cognitive skill data collection used observation guidelines consisting of cognitive dimensions (1) symbolic thinking recognizing concepts, (2) learning problem solving and cause and effect, (3) association and classification. The assessment of cognitive skills used a scale of 1 - 4. The study results concluded an increase in the average value of cognitive skills of kindergarten students aged 5-6 years through the Calistung game. This research implies that teachers' competence in using digital calistung media needs to be improved through in-service training kindergarten students' cognitive skills.